THE INFLUENCE OF SAFETY LEADERSHIP, EFFECTIVE COMMUNICATION, EMPLOYEE COMPETENCE, AND WORK CULTURE ON SAFETY BEHAVIOR AT THE JAMBARAN TIUNG BIRU CEPU CONSTRUCTION PROJECT OF PT ELNUSA FABRIKASI KONSTRUKSI - Boby Satria; Erislan Erislan; Sugiarto Sugiarto (INTECOMS: Journal of Information Technology and Computer Science, 2025)
This study aims to examine the influence of safety leadership, effective communication, employee competence, and work culture on safety behavior. The research population consists of all employees in the construction business unit of the JTB Cepu construction project carried out by PT Elnusa Fabrikasi Konstruksi, totaling 60 people. Data analysis was conducted using a quantitative approach through Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS version 4 software. The results show that safety leadership and effective communication have no significant effect on safety behavior, while employee competence and work culture have a significant effect on safety behavior. These findings indicate that the formation of safe work behavior is more determined by individual capacity and organizational culture rather than structural approaches. Therefore, the company is advised to improve employees’ technical competencies and strengthen the internalization of a safety-oriented work culture.